2014
DOI: 10.1002/2013ms000276
|View full text |Cite
|
Sign up to set email alerts
|

The effect of horizontal resolution on simulation quality in the Community Atmospheric Model, CAM5.1

Abstract: We present an analysis of version 5.1 of the Community Atmospheric Model (CAM5.1) at a high horizontal resolution. Intercomparison of this global model at approximately 0.25 , 1 , and 2 is presented for extreme daily precipitation as well as for a suite of seasonal mean fields. In general, extreme precipitation amounts are larger in high resolution than in lower-resolution configurations. In many but not all locations and/or seasons, extreme daily precipitation rates in the high-resolution configuration are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
257
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(287 citation statements)
references
References 74 publications
(114 reference statements)
26
257
2
2
Order By: Relevance
“…Especially previous studies have demonstrated physical parameterization scheme of climate models also influences simulating precipitation (Im et al 2008;Endo et al 2012;Ali et al 2015). Several studies have argued increasing horizontal resolution dramatically does not improve a climatology of large-scale (Bacheister et al 2013;Wehner et al 2014). Nevertheless, Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Especially previous studies have demonstrated physical parameterization scheme of climate models also influences simulating precipitation (Im et al 2008;Endo et al 2012;Ali et al 2015). Several studies have argued increasing horizontal resolution dramatically does not improve a climatology of large-scale (Bacheister et al 2013;Wehner et al 2014). Nevertheless, Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Such sensitivities are typical in all scales of models. For example, CAM has been shown to be sensitive to both horizontal and vertical resolution and the physics time step used (Bogenschutz et al, 2012;Reed et al, 2012;Williamson, 2013a, b;Wehner et al, 2014). The degradation of SCM simulations when brought to a resolution more realistic for including in a host model like CAM suggests that some more testing and tuning may be necessary; however, the simulations show initial promise.…”
Section: Sensitivity To Time Step Number Of Samples and Vertical Grmentioning
confidence: 99%
“…Multidecadal GCM simulations can now be carried out at grid spacings of about 20 km (Jung et al, 2012;Mizuta et al, 2012;Wehner et al, 2014;Mizielinski et al, 2014;van Haren et al, 2015). This offers the possibility of using a single global physically consistent model in applications that until a few years ago were in the realm of RCM simulations (van der Linden and Mitchell, 2009).…”
Section: Introductionmentioning
confidence: 99%